Frequency of mutations in individuals with breast cancer referred for BRCA1 and BRCA2 testing using next‐generation sequencing with a 25‐gene panel. Issue 1 (3rd September 2014) - Tung, Nadine; Battelli, Chiara; Allen, Brian; Kaldate, Rajesh; Bhatnagar, Satish; Bowles, Karla; Timms, Kirsten; Garber, Judy E.; Herold, Christina; Ellisen, Leif; Krejdovsky, Jill; DeLeonardis, Kim; et al.
Abstract : BACKGROUND: Next‐generation sequencing (NGS) allows for simultaneous sequencing of multiple cancer susceptibility genes and, for an individual, may be more efficient and less expensive than sequential testing. The authors assessed the frequency of deleterious germline mutations among individuals with breast cancer who were referred for BRCA1 and BRCA2 ( BRCA1/2 ) gene testing using a panel of 25 genes associated with inherited cancer predisposition. METHODS: This was a cross‐sectional study using NGS in 2158 individuals, including 1781 who were referred for commercial BRCA1/2 gene testing (cohort 1) and 377 who had detailed personal and family history and had previously tested negative for BRCA1/2 mutations (cohort 2). RESULTS: Mutations were identified in 16 genes, most frequently in BRCA1, BRCA2, CHEK2, ATM, and PALB2 . Among the participants in cohort 1, 9.3% carried a BRCA1/2 mutation, 3.9% carried a mutation in another breast/ovarian cancer susceptibility gene, and 0.3% carried an incidental mutation in another cancer susceptibility gene unrelated to breast or ovarian cancer. In cohort 2, the frequency of mutations in breast/ovarian‐associated genes other than BRCA1/2 was 2.9%, and an additional 0.8% had an incidental mutation. In cohort 1, Lynch syndrome‐related mutations were identified in 7 individuals. In contrast to BRCA1/2 mutations, neither age at breast cancer diagnosis nor family history of ovarian or young breast cancer predicted for other mutations. The frequency of mutations in genes other than BRCA1/2 was lower in Ashkenazi Jews compared with non‐Ashkenazi individuals ( P =.026). CONCLUSIONS: Using an NGS 25‐gene panel, the frequency of mutations in genes other than BRCA1/2 was 4.3%, and most mutations (3.9%) were identified in genes associated with breast/ovarian cancer. Cancer 2015;121:25–33 . © 2014 American Cancer Society . Abstract : Using a next‐generation sequencing 25‐gene panel, the frequency of mutations for patients with breast cancer in genes other than BRCA1/2 is 4.3%, and most of the mutations (3.9%) are in genes associated with breast/ovarian cancer. Approximately half of patients with mutations in genes other than BRCA1/2 are identified in moderate‐penetrance genes for which the efficacy of medical management is less well defined.